2019
DOI: 10.1002/cdq.12205
|View full text |Cite
|
Sign up to set email alerts
|

Student Veteran Career Transition Readiness, Career Adaptability, and Academic and Life Satisfaction

Abstract: Student military veterans pursuing higher education present with unique career development needs. To better understand these needs, the authors conducted an exploratory study to examine career transition readiness, career adaptability, academic satisfaction, and satisfaction with life among 134 student military veterans (34 women, 100 men). Results indicated statistically significant positive correlations between satisfaction with life scores and scores on measures of career transition readiness and career ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 17 publications
0
22
3
Order By: Relevance
“…Finally, readiness is positively associated with satisfaction [ 73 ] and optimism [ 74 , 75 ] and negatively associated with psychological distress [ 76 ]. Some studies specifically focused on career transition readiness in college students showed that career adaptability was among its predictors [ 77 ] and there are positive correlations between, career readiness, career adaptability, and satisfaction with life [ 78 ]. In the university context, it seems that one of the most important factors associated with the decrease in self-efficacy in a career search and the increase in psychological distress is the reduction of certain psychological resources such as readiness, confidence, and support in a career transition [ 79 ].…”
Section: Literature Review: the Role Of Career Adaptability Careementioning
confidence: 99%
“…Finally, readiness is positively associated with satisfaction [ 73 ] and optimism [ 74 , 75 ] and negatively associated with psychological distress [ 76 ]. Some studies specifically focused on career transition readiness in college students showed that career adaptability was among its predictors [ 77 ] and there are positive correlations between, career readiness, career adaptability, and satisfaction with life [ 78 ]. In the university context, it seems that one of the most important factors associated with the decrease in self-efficacy in a career search and the increase in psychological distress is the reduction of certain psychological resources such as readiness, confidence, and support in a career transition [ 79 ].…”
Section: Literature Review: the Role Of Career Adaptability Careementioning
confidence: 99%
“…Given that the CTI total score emerged as a strong predictor of scores on the MLQ-P subscale, researchers may want to explore this finding in greater depth by examining the CTI subscales, that is, Decision-Making Confusion, Commitment Anxiety, and External Conflict, and their relationship to the presence of meaning in a student veteran's life. On the basis of this study's findings and other recent studies (e.g., Blackburn & Owens, 2015;Ghosh et al, 2019), it may be useful to explore how other career readiness (e.g., career adaptability, self-efficacy) and selfassessment (e.g., differentiation, values) constructs are related to meaning and purpose in student veterans' lives. The Career Transitions Inventory (Heppner, 1998) could be used to investigate how student veterans experience life transitions in relation to other career development and mental health factors.…”
Section: Implications For Research and Practicementioning
confidence: 80%
“…Interventions aimed at targeting negative career thoughts and depressive symptomatology may enhance student veterans' self‐report of meaning and purpose in their lives. Having conversations about how student veterans' view the concepts of meaning and purpose in their lives may also be useful, in addition to assessing for depressive symptomatology and protective factors such as life satisfaction (Ghosh et al, 2019), satisfaction with work, intimate relationships, nonfamily relationships, and leisure activities (Bryan et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Career adaptability (CA), a central construct of career construction theory ( Savickas, 2002 ; Savickas et al, 2009 ), represents individuals’ psychosocial resources that help one to fit environmental change ( Savickas, 1997 ). Indeed, CA has been shown empirically to be a significant and universally valid factor that enables individuals to facilitate psychological adjustment and achieve adaptation goals (e.g., Guan et al, 2013 ; Fiori et al, 2015 ; Hirschi et al, 2015 ; Ghosh et al, 2019 ; Urbanaviciute et al, 2019 ), thus emerging vocational research on career construction theory has started to explore the drivers of CA ( Coetzee and Harry, 2013 ; Zacher, 2014 ; Shin and Lee, 2016 ; Autin et al, 2017 ; Obschonka et al, 2018 ; Pajic et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%